Pharmacokinetics of nebulized and subcutaneously implanted terbinafine in cottonmouths (Agkistrodon piscivorus). Issue 5 (6th April 2017) - Kane, L. P.; Allender, M. C.; Archer, G.; Leister, K.; Rzadkowska, M.; Boers, K.; Souza, M.; Cox, S.
Abstract : Ophidiomyces ophiodiicola, the causative agent of snake fungal disease, is proposed as a serious threat to the conservation of several snake populations. The objective of this study was to determine the pharmacokinetic parameters of terbinafine administered through nebulization and a sustained subcutaneous implant as potential treatments of Ophidiomyces in reptiles. Seven adult cottonmouths ( Agkistrodon piscivorus ) were used in single‐dose trials. Each snake was nebulized with terbinafine (2 mg/ml) for 30 min and had blood collected before nebulization and up to 12 hr after nebulization. Following a 5‐month washout, the same snakes were administered a subcutaneous implant containing 24.5 mg terbinafine; blood was collected at baseline, 1 day postimplant placement, and then once weekly for 9 weeks. Plasma for both studies was analyzed by high‐performance liquid chromatography. The mean plasma concentrations of nebulized terbinafine peaked between 0.5 and 4 hr. The subcutaneously implanted terbinafine reached therapeutic concentrations on day 1 and maintained therapeutic for over 6 weeks. These methods and doses are recommended as potential treatment options for snake fungal disease in reptiles.